Perbedaan Pendidikan Kesehatan Menggunakan Metode Ceramah Dan Audiovisual Terhadap Tingkat Pengetahuan Dan Sikap Perawatan Karies Gigi Anak Di Wilayah Puskesmas Wonosegoro II - Lubis, Fatahillah Sang, Sulastri S.Kp,M.Kes, Ns. Arief Wahyudi Jadmiko, M.Kep (2016)
Keeping sanitations of tooth and mouth should be done early on. It is intended for minimizing caries. Health education using speech method and audio visual is intended for improving children's knowledge about caries so that they know how to keep dental - hygiene and how to improve good attitude in keeping sanitations of tooth and mouth. The objective of this research is identifying differences between health education using speech method and audio visual toward level of knowledge and attitude of children caries care at Puskesmas Wonosegoro II. Type of this research is quantitative research with quasi experimental method. Furthermore, design of this research is two group pretest - posttest. The research sampling is 30 students at the 5th grade of SD Gunungsari II and 30 students at the 5th grade of SD Repaking I Wonosegoro, Boyolali. The writer uses simple random sampling as the method of collecting data in this research. This research applies questioner as instrumental research. In analyzing the data, the writer uses paired sample test and independent sample test as comparative experiment. According to research finding, pre-test of speech method knowledge group is 40% and post-test of speech method knowledge group is 70%. It is included into sufficient category. Then, pre-test of knowledge audio visual group is 40 %. It is included into fewer categories. Post-test of knowledge audio visual group is 63, 3 %. It is included into sufficient category. Besides, a lot of pre test of attitude either speech method or audio visual included into negative category. However, post-test increases to be better. The finding of the second of paired sample test of two groups in the similarity media at the level of knowledge is getting score p < 0, 05. The finding of the second of paired sample test of two groups in the similarity media at their attitude is getting score p < 0, 05. The finding of independent sample test is p < 0, 05. It concludes that there are knowledge and attitude of student in caries caring. Therefore, there is a difference influencing between speech method and audio visual toward knowledge. However, it does not difference of influence toward attitude.